A SYSTEMATIC REVIEW OF CONTEMPORARY AND INNOVATIVE WAQF SOURCES: CASH AND SERVICE WAQF - Rahmalan, Muhammad Tariq; Abu Hussin, Mohd Fauzi (Jurnal Syariah, 2021)
Waqf has been one of the major sources of public financing in Islamic tradition. Since early Islam, waqf serves the needs of the ummah in various realms, including education, social development and public needs. Traditionally, waqf has been in the form of fixed and tangible assets. Up until recently, cash waqf has been proposed as one of the sources of waqf. On the other hand, there has been also a suggestion to innovate the practices of waqf in order to assure that they meet the current challenging world. One of the new innovatives of funding waqf sources apart from cash waqf is Service Waqf. Giving this background, this paper endevour to do a systematic review analysis of the Service Waqf as well as well established cash waqf practices as innovatie way for diversifying waqf source in Malaysia. In reviewing the topics systematically, this paper gathered all related articles from Emerald Insight, Google Scholars, Jstor, and Scopus databases. Relevant journal articles were being searched via the internet in several database sources using advanced searching features available in those database based on specific keywords. The relevant journals were selected based on the latest findings which had been published between year 2010 until 2020. From the systematic review analysis, 20 journal articles regarding ethical issues in gamification were filtered and selected using PRISMA statement. Findings from this systematic analysis show that issues pertaining to the cash waqf were among the major discourse in the waqf innovation. Much have been emphasised on the waqf management and governance and also the reason waqf application in a institution. Less has been given into the service waqf and its benefits to communities.